ASSESSMENT OF PUBLIC PRIMARY SCHOOLS FACILITIES FOR THE IMPLEMENTATION OF E-LEARNING PROGRAMMES IN EMUHAYA SUB-COUNTY KENYA - Tsindoli, Sylvia; Opati, Dishon William (IJRDO- Journal of Educational Research, 2018)
The purpose of this study was to assess public primary schools facilities for the implementation of e-learning programmes in Emuhaya Sub-county in Kenya. Two specific objectives guided this study as follows: To establish the physical structures available to facilitate e – learning and quantities of electronic hardware and software available in schools. Simple random sampling method was used to select 25 public primary schools from 83 schools in the sub-county. The sample size comprised 200 class teachers as respondents selected from middle and upper primary. Questionnaires were administered to class teachers and their responses presented in frequencies and percentages for the purpose of data analysis. The findings of the study revealed that 95% of public primary schools did not have computers and 79% had no electricity. Based on the findings of the study, there are no appropriate physical infrastructures in public primary schools to ensure smooth implementation of the programme. The schools do not have sufficient funds for construction of computer laboratories. Lack of computers, laboratories and guidelines in schools are identified as impediments to implementation of e – learning programmes. It poses a hindrance to teachers who have trained in ICT and may not practice it. Arising from the findings the study recommends that the government should provide funds through the budget allocations and ensure schools acquire modern computer laboratories with supply of electricity. Schools may also send proposals to CDF for funding of computers and modern e-learning classrooms. Security to curb theft and vandalism of equipment should be provided.